Human Resources Performance in Public Services Through Strengthening the Work Environment, Self-Leadership, and Self-Efficacy - Utami, Mega; Jusriadi, Edi; Maklassa, Dg. (Manunggal Halim Jaya, 2026)
This study analyzes the influence of work environment, self-leadership, and self-efficacy on employee performance in providing public services. This study raises various experiences and new knowledge the author did not have before. Efforts to improve problems related to aspects of human resource management to obtain employees with quality performance can increase the knowledge and insight of researchers regarding the importance of performance and the role of the work environment, self-leadership, and self-efficacy. The type of research is quantitative research using a survey approach by providing questionnaires to test the influence of work environment variables, self-leadership, and self-efficacy on the Performance of Employees. The population used by the researcher was all state civil servants at the Ministry of Religion Office of Mamuju Regency, namely 491 employees. The number of samples was determined using the Slovin formula between 100 and 200, with the technical analysis being path analysis. The study results showed that the work environment, self-leadership, and Self-efficacy positively and significantly affect employee performance.